Management of Nasopharyngeal Carcinoma Patient in General Hospital Haji Adam Malik Medan (TALENTA PUBLISHER, 2021)
Introduction: Nasopharyngeal carcinoma (NPC) is a malignancy of squamous cells on nasopharyngeal epithelial layer with Rosenmuller fossa with a high incidence especially in Asian region. There is three different histologic subtypes, namely squamous cell carcinoma, nonkeratinizing carcinoma, and undifferentiated carcinoma. Principle of management NPC is radiotherapy because of this kind of carcinoma highly radiosensitive and is the mainstay of treatment for all stages. But in advance case, we need combinatio of radiotherapy and chemotherapy Case report: We report a patient which came to the ENT-Head and Neck Surgery Outpatient Clinic of General Hospital Haji Adam Malik Medan with complaint of tinnitus in the right ear and nasal congestion on the right side. The patient then performed a contrast-enhanced nasopharyngeal MSCT scan with the result: T2aN0M0. The histopathology results : Non Keratinizing Squamous Cell Carcinoma. The patient was given 70 gy of Concurent Chemoradiation (CRT) followed by adjuvant chemotherapy with Cisplatin and 5 Flourouracil (FU). Conclusion: There was no visible mass on the nasopharynx after using this combination Radiation and Chemotherapy